Emotion-Network Density in Major Depressive Disorder. (March 2015) - Pe, Madeline Lee; Kircanski, Katharina; Thompson, Renee J.; Bringmann, Laura F.; Tuerlinckx, Francis; Mestdagh, Merijn; Mata, Jutta; Jaeggi, Susanne M.; Buschkuehl, Martin; Jonides, John; Kuppens, Peter; Gotlib, Ian H.
Major depressive disorder (MDD) is a prevalent disorder involving disturbances in mood. There is still much to understand regarding precisely how emotions are disrupted in individuals with MDD. In this study, we used a network approach to examine the emotional disturbances underlying MDD. We hypothesized that compared with healthy control individuals, individuals diagnosed with MDD would be characterized by a denser emotion network, thereby indicating that their emotion system is more resistant to change. Indeed, results from a 7-day experience sampling study revealed that individuals with MDD had a denser overall emotion network than did healthy control individuals. Moreover, this difference was driven primarily by a denser negative, but not positive, network in MDD participants. These findings suggest that the disruption in emotions that characterizes depressed individuals stems from a negative emotion system that is resistant to change.